USING EXERGY LOSS PROFILES AND ENTHALPY-TEMPERATURE PROFILES FOR THE EVALUATION OF THERMODYNAMIC EFFICIENCY IN DISTILLATION COLUMNS - Faria, S. H. B.; Zemp, R. J. (Revista de Engenharia Térmica, 2005)
In this work the temperature-enthalpy profile and the exergy loss profile are used together to improve thermodynamic efficiency of distillation columns, by identifying possible benefits of using side exchangers. The method proposed is to compute the exergy loss profile and to analyse the distribution of the losses across the column stages. The present work aims at applying the stage-by-stage exergy analysis to the distillation of non-ideal mixtures, e.g. methanol/water. For these systems the use of thermodynamic excess properties is required: Gibbs free energy for phase equilibrium and enthalpy of solution for energy balance. Initial studies showed that the enthalpy of solution has a small effect on the overall energy balance of the distillation column, but a significant impact on the exergy loss profiles. Some profiles even showed a violation of the second law of thermodynamics, with entropy being destroyed on some stages, clearly indicating that a wrong approach to exergy calculation was being used.A model for exergy calculations of non-ideal solutions is presented. The exergy values so computed are then checked by a consistency test, using the reversible column profile. Finally, the exergy procedures are used to study a typical methanol/water distillation columns, where the exergy profiles are used to identify scope for intermediate heat exchange.